Kuracja . The Cure - Cuske, Maciej (Poland, 2004)
Duration: 00:56:00 The imposing building of baroque grandeur is a temporary resting-place: a spa named Ciechocinek – very well known all across Poland. The guests stay here for a few days or weeks, far from their everyday life, their relatives and friends: here they are supposed to recuperate and heal, far from everything that made them sick. Here there’s no time-clock – life has a different rhythm defined by sleeping, eating, healing. The camera follows the summer-guests through the foyers of the spa, through the parks; watches them sitting on the benches – observed observers. Extremely long takes and the absence of a musical score or comment fit well with the quiet of the place. But even when it sometimes seems that nothing is happening, life has not stopped – on the contrary, it demands its due. The process of healing can also be seen during activities: people flirt, dance and celebrate – and, yes, also drink and quarrel. This is how this life – seemingly removed from normality – nevertheless mirrors what happens beyond the green lawns and avenues.